A star of the airwaves: Peter Lorre master of the macabre and American radio programming. (21st July 2008) - Thomas, Sarah
The article argues that within analyses of star performers from the classical Hollywood period, the role played by the medium of radio has been significantly underestimated. Building upon new developments in star discourses which question the role of the cinema as the dominant medium in the creation of star personae, this article examines the relationship between Hollywood and American broadcast media through a study of the multi-medial persona of Peter Lorre in order to suggest that the macabre star persona associated with Lorre has been erroneously attributed to his cinematic career at the expense of a consideration of his radio career. Central to Lorre's public persona was the nature of his employment on American radio between 1936 and 1964. The article discusses the three types of appearances made by the actor: as a star performer in horror programming; his position as host of horror series; and his celebrity cameos on popular shows. It explores how Lorre's extensive radio work was reliant upon certain consistent modes of representation which had the potential to greatly influence public awareness of the performer and helped to cement his nefarious star persona to a far greater degree than his film roles or screen performances.